Sentidos e significados constituídos por um diretor de escola voltada aos anos iniciais do ensino fundamental e vinculada ao Programa Ensino Integral (PEI) quanto ao seu papel como mediador de conflitos em sala de aula - Vieira, Regiane de Araújo (2018)
The objective of this study was to understand the senses and meanings of a IEP director in relation to his / her role as mediator of classroom conflicts and specific objectives: a) to know the personal and professional life history of the investigated subject; b) identify aspects that shows changes in the subject’s performance. The data collection took place through a semi-structured interview through a visit of the researcher at the research subject school whose modality was composed of some closed questions with the purpose of characterizing the socioeconomic profile of the research subject and open questions about the object of study. During the analysis of the data collected through the interview, we realized the need to complement the research with some questions. Therefore, due to the difficulty in finding the subject of the research personally, since it was outside Sao Paulo, we conducted this second interview remotely. The subject of the research was a school director from the research site that attends the integral education, initial years, of the São Paulo state network. These interviews were recorded and transcribed by us for analysis purposes. For the analysis reference, we proceeded the steps as proposed by Aguiar and Ozella (2013), “nuclei of meaning”. Method: these nuclei were analyzed in the light of socio-historical theory and were based on historical and dialectical materialism. The study reveals that the investigated subject recognizes the importance of the role of the director in the mediation of conflicts that emerge from the classroom, that this mediation, besides serving as support to the teacher, is shown as modeling for the actions of the latter in which he contemplates the dialogue as main strategy. The present study also reveals that, although the director recognizes the importance of this role of mediator, it coexists with tasks that “divide” him between the administrative and the pedagogical tasks, but even though, when prioritizing mediation actions that involve conflicts, it is possible to turn difficulties into opportunities for growth and development of all actors in the school environment. In this way it can be concluded that there is a need for training of the director in which the use of dialogue is used to articulate administrative activities and pedagogical concerns. And furthermore because good interpersonal relationships are fundamental in one case as in the other